SOCIAL PROBLEMS IN THE POEM "DI NEGERI AMPLOP" BY A. MUSTOFA BISRI (SEMIOTIC STUDY) RIFFATERRE - Nia Mubarokah; Dyah Wijayawati (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The poem “Di Negeri Amplop”, has a background of social problems conveyed by the author. The formulation of the research problem, namely: (1) how is the meaning and hypogram in the poem “Di Negeri Amplop” by A. Mustofa Bisri; and (2) hhat are the social problems contained in the collection of poetry “Di Negeri Amplop” by A. Mustofa Bisri. The objectives are: (1) to describe the meaning and hypogram in the collection of poems “Di Negeri Amplop” by A. Mustofa Bisri; and (2) to describe the social problem contained in the collection of poems "Di Negeri Amplop" by A. Mustofa Bisri. This research is in the form of a qualitative descriptive. The data in this study are in the form of a poem containing social problem entitled “Di Negeri Amplop”. Collecting data using library method. Data analysis using semiotic method. The results of this study indicate the meaning of bribery, corruption, collusion, and the existence of poor people. This meaning shows the existence of social problems of crime in the form of bribery.